The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fped.2022.881516
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neurodevelopmental Characteristics of Enterovirus and Parechovirus Meningitis in Neonates

Abstract: BackgroundNon-polio-enteroviruses (EV) and human parechoviruses (HPeV) are small RNA viruses, which in newborns cause infections with a wide range of severity. Today molecular biology tools allow us to diagnose viral meningitis in neonates, sparing patients from useless antibiotics. Data on neurodevelopmental outcome of children who contract enterovirus meningitis in early childhood are still limited in the literature.AimsTo evaluate the neurodevelopmental outcome of newborns with documented enterovirus and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…and HpEV are major causes of infection in children and may present with a variety of clinical manifestations [1][2][3][4]6]. In neonates and young infants, EV and HpEV have been reported to cause sepsis-like illnesses and severe CNS infections.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…and HpEV are major causes of infection in children and may present with a variety of clinical manifestations [1][2][3][4]6]. In neonates and young infants, EV and HpEV have been reported to cause sepsis-like illnesses and severe CNS infections.…”
Section: Discussionmentioning
confidence: 99%
“…In neonates and young infants, EV and HpEV have been reported to cause sepsis-like illnesses and severe CNS infections. It has been reported that the younger the patient, the more severe the clinical manifestations [2,4,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations